TINJAUAN YURIDIS TERHADAP PEMBATALAN MEREK TERDAFTAR DALAM KASUS MEREK AYAM GEPREK BENSU PASCA PUTUSAN MA NOMOR 575 K/PDT.SUS-HKI/2020 - Irma Nurul Hasyanah; Maria Maya Lestari; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Intellectual Property Rights have a fairly broad scope, including brands. Brands have animportant role in identifying the goods or services of a particular seller or group of sellers anddistinguishing them from the goods or services produced. Thus, it is very important to registerthe trademark of the Ministry of Law and Human Rights Cq. Directorate General ofIntellectual Property in order to obtain legal protection. Mark provisions are regulated in theLaw of the Republic of Indonesia Number 20 of 2016 concerning Marks and GeographicalIndications. Article 72 to Article 79 regulates the abolition and cancellation of registeredmarks on the initiative of the minister. However, if this action is not carried out based on theapplicable laws and regulations, it can lead to unlawful acts.This research is a normative legal research with a normative juridical approach bycritically analyzing the cancellation and abolition of the I AM GEPREK BENSU SEDEPBENER brand by the Ministry of Law and Human Rights Cq. Jakarta Directorate General ofIntellectual Property which does not implement decision Number 56/Pdt.Sus-HKI/Merek/2019/PN Niaga Jkt.Pst Central Jakarta Commercial Court which has permanentpower (incraht).The results of this study show the first: the act of canceling and deleting the I AMGEPREK BENSU SEDEP BENER brand belonging to Yangchent from the general list ofbrands by the Ministry of Law and Human Rights Cq. Jakarta's Directorate General ofIntellectual Property has administrative defects and has resulted in unlawful acts. In DecisionNumber 56/Pdt.Sus-HKI/Merek/2019/PN Niaga Jkt.Pst the Central Jakarta Commercial Courthas decided that Yangchent is proven to be the first owner of the I AM GEPREK BENSUSEDEP BENER brand which is officially registered in the general register of marks andordered to carry out cancellation and deletion of the GEPREK BENSU mark, the owner ofRuben, from the general register of marks. In principle, the court's decision is a reflection ofthe values of justice and the essential truth with sufficient evidence and facts. Second: the act ofdeleting and canceling the I AM GEPREK BENSU SEDEP BENER brand by the Ministry ofLaw and Human Rights Cq. The Directorate General of Intellectual Property of Jakartaresulted in the mark being removed from the general register of trademarks, the end of legalprotection for the mark, the end of cooperation with the licensee of the mark, the occurrence ofmaterial and immaterial losses of the brand holder. Thus the business development of PT. I AMGEPREK BENNY SUJONO no longer has legal protection, especially in the culinary businessof I AM GEPREK BENSU SEDEP BENER.Keywords : Brand – Deletion – Cancellation